SEXUAL ABUSE CLAIMS IN CANADA AND THE ISSUES FOR INSURERS - Bell, Robert B. (Assurances)

(untitled) (HEC Montréal, 1998)
The purpose of this article is to examine the scope of sexual abuse from the standpoint of the Canadian Courts and to briefly comment on the actual legal theories. The author explains that claims from sexual abuse generally arise from what has been characterized as "power dependency relationships", which include relations between parent and child, physician and patient, clergy and penitent, professor and student, solicitor and client and employer and employee. The battleground is always whether the institution is liable, and quite rarely, whether the perpetrator is liable. A large plan of the article is focused on insurance wordings and defence issues for insurers. Insurers face uncertainty in terms of how the courts will deal with claims, and, in addition, face uncertainty as to how the courts will decide issues with respect to defence and indemnity obligations.